Using Network Pharmacology to Clarify the Therapeutic Mechanism of Hataagqi-19 Hot Compress Therapy in Rats with Lumbar Disc Herniation - Aruhan; Dorjsuren, Byambasuren; Chimedtseren, Chimedragchaa; Damba, Tsend-Ayush (Central Asian Journal of Medical Sciences, 2021)
Objective: This study aims to determine the primary efficacy of traditional medicine treatment of Lumbar disc herniation (LDH) and the effect of Hataagqi-19 hot compress (H19+HC) therapy on LDH rats. Methods: Referencing ancient books of Mongolian medicine, we studied the theoretical basis of Mongolian medicine to treat LDH. We performed operations to establish a model of SD rats with LDH treated with H19+HC. Paw withdrawal threshold (PWT) was detected, serum TNF-α, IL-6, and IL-1β were measured by ELISA, and immunohistochemical staining was used to measure IL-6, CD68, and IgG. Results: The medicinal properties of the drugs for the treatment of LDH are mainly dry “Xieriwusu,” heat-clearing, and suppressing “Heyi” medicine. The PWT value, serum TNF-α, IL-6, IL-1β and tissue IL-6, CD68, IgG of H19+HC was lower than that of the control group. The nucleus pulposus of the H19+HC was significantly smaller than that of the control group. The positive staining result in the main inflammatory cells of the lesion was CD68. Conclusions: Mongolian medicine treatment of LDH is based on the dry “Xieriwusu,” heat-clearing, and suppressing “Heyi” efficacy. The H19+HC therapy follows this efficacy and has the effects of improved abnormal behavior, analgesic, anti-inflammatory, and reabsorption of the nucleus pulposus.